2022
DOI: 10.3390/plants11081028
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, Antioxidant Potential, and Cytotoxicity Evaluation of Traditionally Used Artemisia absinthium L. (Wormwood) Growing in the Central Region of Saudi Arabia

Abstract: Artemisia absinthium, a plant distributed worldwide, has been reported for its numerous traditional uses, and its phytoconstituents have been investigated in several previous publications. The current study was designed to investigate the chemistry and quality; i.e., the antioxidant and cytotoxic activities, of A. absinthium volatile oil from plant species growing in the central area of Saudi Arabia compared to reported data for the plant growing in other parts of the world. Gas chromatography–mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Using the method of Zengin et al [ 78 ] with modification, the ability of compounds to chelate iron compared to the EDTA was estimated. To inchoate the color, a compound solution in DMSO (2 with a final concentration of 1 mM) plus ferrous chloride (25 μL, 2 mM, FeCl 2 ) was added to 100 μL of ferrozine.…”
Section: Methodsmentioning
confidence: 99%
“…Using the method of Zengin et al [ 78 ] with modification, the ability of compounds to chelate iron compared to the EDTA was estimated. To inchoate the color, a compound solution in DMSO (2 with a final concentration of 1 mM) plus ferrous chloride (25 μL, 2 mM, FeCl 2 ) was added to 100 μL of ferrozine.…”
Section: Methodsmentioning
confidence: 99%
“…The assay was carried out according to the reported method. 38 In a 96-well plate, the TPTZ working reagent (190 μl) composed of acetate buffer (300 mM PH = 3.6), TPTZ (10 mM in 40 mM HCl), and FeCl3 (20 mM) was added to 10 μl of the plant extract, and the mixture was kept at RT for 30 min before being measured at 593 nm. The FRAP extract activity was measured as mg Trolox equivalent.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that octadecanoic acid-2, 3-dihydroxypropyl ester exerts numerous pharmacological effects such as antioxidant, hepatoprotective, anti-eczemic, hypocholesterolemic, and antihistaminic properties (Fadeyi et al, 2015). Hexadecanoic acid-2-hydroxy-1-(hydroxymethyl) ethyl ester possesses antioxidant, hypocholesterolemic, nematocidal and antiandrogenic properties (Tulika and Mala, 2017 The presence of terpineol in the essential oil of A. absinthium L. has been reported (Mohammed, 2022;Pan et al, 2013). Bicyclo[2.2.1]heptan-2-one was present in the CMMEL of A. absinthium L. and reported as a good fragrance agent (Krishnamoorthy et al, 2018).…”
Section: Antibacterial Studies 251 Type Of Bacteria and Cultures Usedmentioning
confidence: 99%